Understanding green consumption: exploring the role of socially responsible attitudes in sustainable buying behavior - Selim Çam; Murat Fatih Tuna; Talha Bayır (Discover Sustainability)
Abstract It is known that consumers are becoming more conscious of environmentally friendly consumption every year. Increasing consumption awareness has created a mass of consumers with socially responsible attitudes. Especially in recent years, concepts such as carbon footprint, environmentally friendly products, and green and sustainable buying have become important research topics. Within the scope of the research, the relationship between green consumption intention (GC-I) and economic value (EcV), environmental value (EnV), and social value (SV) level was measured first. Secondly, the mediating effect of socially responsible consumption attitude (SRC-A) on the relationship between these variables was measured. Thirdly, the effects of sustainable buying behavior (SBB) were measured. A convenient sampling method was used in the study, and the sample population included 314 individuals. The online survey method was used to collect data for the analysis. The Smart-PLS was used to evaluate the hypothesized relations between the items in the structural model. Confirmatory factor analysis (CFA) was used at the outset of the structural equation modeling (SEM) method to assess the measurement model's validity and reliability. Using the SmartPLS, regression analyses were conducted through the model's structural validation phase to determine the overall fit and hypothesized relationships. The findings indicated that SRC-A mediates the relationship between EnV, SV, and GC-I. Furthermore, GC-I also mediates the relationship between EcV, EnV, SV, SRC-A, and SBB. As a result, this research provides a variety of practical and theoretical implications that could assist in clarifying consumers' SRC-A, GC-I, and SBB.